Effectiveness of TC-325 (Hemospray) for treatment of diffuse or refractory upper gastrointestinal bleeding: a single center experience - Cahyadi, Oscar; Bauder, Markus; Meier, Benjamin; Caca, Karel; Schmidt, Arthur (Endoscopy International Open, 2017)
Background and study aims: TC-325 (Hemospray, Cook Medical) is a powder agent for endoscopic hemostasis in patients with upper gastrointestinal bleeding (UGIB). Although most publications are based on case-reports and retrospective studies, data on efficacy are promising. Here we report our experience with TC-325 for diffuse or refractory UGIB. Patients and methods: Data on patients receiving TC-325 for endoscopic hemostasis from November 2013 to February 2017 at our center were analyzed retrospectively. Primary endpoints were technical success (successful immediate hemostasis) and clinical success (effective hemostasis and no recurrent bleeding). Secondary endpoints were recurrent bleeding within 3 and 7 days, hospital mortality and TC-325 associated complications. TC-325 was used for bleeding not amenable to standard endoscopic treatment (e. g. diffuse bleeding) or as salvage therapy after failure of conventional methods. Results: Fifty-two patients received TC-325 treatment. Most of the patients were treated for peptic ulcer bleeding (18/52 patients, 34.6 %) and post-interventional bleeding (13/52 patients, 25 %). Hemospray was used in 23/52 (44.2 %) patients as monotherapy and in 29/52 (55.8 %) patients as a salvage therapy. Application of the powder on the bleeding source was successful in all patients with no therapy-related adverse events (AEs). Immediate hemostasis was achieved in 51/52 (98.1 %) patients. Recurrent bleeding within 3 and 7 days was observed in 22/51 and 25/51 patients respectively (43.1 % and 49 %). The overall clinical success was 56.9 % on day 3 and 51 % on day 7. Total mortality was 15.4 % (8 patients), bleeding associated mortality was 3.8 % (2 patients). There were no therapy-related AEs. Conclusions: TC-325 showed a high technical success rate as monotherapy for bleeding sources not amenable to standard methods or as an “add-on” therapy after unsuccessful hemostasis. However, rebleeding was frequent in this cohort and further studies are warranted to exactly define a treatment algorithm for TC-325 use.
Gesehen am 11.11.2024